Wearable system for monitoring of oxygen concentration in breath based on optical sensor - Lopez-Ruiz, N.; Lopez-Torres, J.; Carvajal Rodriguez, M.A.; Perez de Vargas-Sansalvador, I.; Martinez-Olmos, A. (IEEE Sensors Journal, 2015)
This paper reports the development of a compact, portable prototype for the determination of gaseous oxygen in breath. This system is fully wearable, it can be worn by the user as an armband where the electronics are placed, i.e., connected to a mouthpiece where the breath is sensed. The prototype is based on an optical luminescent sensor consisting of a stabilized porphyrin dye directly deposited onto a color detector. The sensor response, when it is optically excited, is quenched by the surrounding oxygen. The intensity of the generated luminescence is registered by means of a digital color detector whose output data correspond to the coordinates of the RGB color space. For this particular optical sensor, the red coordinate is directly related to the concentration of O2, and it is sent to a remote device such as a smartphone or tablet by a Bluetooth link. An application for Android operative system has also been developed for data visualization and analysis. Employing this novel system, a high resolution in the range of few parts per billion in the determination of oxygen can be achieved.